Effect of pH and Temperature on The Binding of a Fusion Phage to Newcastle Disease Virus - Wen, Siang Tan; Ramanujam, Priadarishni; Nathan, Sheila; Yusoff, Khatijah (2004)
A fusion phage carrying the peptide sequence CTLTTKLYC was selected from a disulfide constrained phage display random peptide library against Newcastle disease virus (NDV) strain AF2240. The binding affinity of the phage for AF2240 is both pH and temperature-dependent with optimal binding occurring at pH 4 and 4oC respectively. No binding was observed at pH 12. Binding decreased with temperatures above 4oC until it was completely abolished at 80oC. The results suggest that the fusion activity of the virus is promoted in acidic conditions.